Common Perceptions of Standard Precautions and Bloodborne Diseases among School Nurse Teachers in Japan - Koike, Yuji; Miyazawa, Miho; Hirohara, Toshie (International Journal of Pediatrics and Child Health, 2020)
Objective: To elucidate the common perceptions of standard precautions and bloodborne diseases, as represented by hepatitis B virus (HBV) and C virus (HCV) infections, among school nurse teachers in Japan. Material and methods: We conducted a questionnaire survey targeting school nurse teachers who were employed at public elementary or junior high schools. The questionnaire had 2 categories: awareness and implementation of standard precautions in the school setting and the other was awareness and provision for bloodborne diseases. Results: A total of 63 school nurse teachers were enrolled in the study. Almost all (96.8%) the school nurse teachers had sufficient knowledge of standard precautions and bloodborne diseases according to the responses. When attending students with a common cold or gastroenteritis, all respondents washed their hands thoroughly, and most of them (92.3% and 89.7%, respectively) wore a facemask. They wore gloves more frequently when attending students with gastroenteritis than when attending those with a common cold. Thirty-one (49.2%) had examinations for HBV and 21 (33.9%) for HCV. Only 11 respondents (18.3%) received an HBV vaccination. Discussion: This study shows that the actual usage of measures for infection prevention and control (IPC) remained incomplete, partly because of the insufficient personal protective equipment in the schools. The appropriate implementation of IPC in the school environment should be done as soon as possible. As school nurse teachers continue to address many pathological agents, they should strictly use standard precautions whenever attending to students. Further investigations in these areas are required.